Jack takes the cake - McGee, Marni; Regan, Dana ([Mahwah, NJ] : Troll, 1998)
Young Jack has no common sense. Does Jack have pudding where his brains should be?
K-Grade 2.
13 34
Keywords: Dogs -- Fiction; Grandmothers -- Fiction; Early readers